Ketahanan pangan pada era globalisasi dan otonomisasi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Food security deals with food availability, accesscibility and stability. Food availability can be from domestic production and import. Although the production of cereals in developing countries almost equal to the production in developed countries, the much greater population of almost 79 % of the world population, the self sufficiency rate of cereals in developing countries is only 91% and to be net importer, while the self sufficiency rate of the developed countries, are more than 100 % (108 %). There are some exception for several developing countries to be big rice exporters such like Thailand, Vietnam, India, China and Pakistan. Cereal staple foods in developing countries is dominated by rice especially in East and South Asia, includes Indonesia. International rice market is characterized with oligopolistic since only six big exporting countries supllying the international rice market. After experiencing rice self sufficiency in 1984 â 1994 Indonesia have been net rice importer again, even in 1998 21% of marketed rice ini the world market were imported by Indonesia. There should be a policy to increase production to a certain rate of rice self sufficiency that will not influence the world rice market equilibrium. The food accessibility depend closely on the wider economic condition such as income distribution, poverty and unemployment, Government intervention is needed toreduce instability including to protect from the international market instability by flexible tariff. Stabilizing the seasional price fluctuation by floor price and ceiling price policy combined with buffer-stock policy had been successful. However, there should be a modified policy toward more liberized without import monopoly.